Population-Based Estimation of Dental Caries and Periodontal Disease Rates of Gravid and Recently Postpartum Women in Lilongwe, Malawi - Antony, Kathleen M.; Kazembe, Peter N.; Pace, Ryan M.; Levison, Judy; Mlotha-Namarika, Jesse; Phiri, Henry; Chiudzu, Grace; Harris, R. Alan; Aagaard, Joshua; Twyman, Nicholas; Ramin, Susan M.; Raine, Susan P.; Belfort, Michael A.; Aagaard, Kjersti M. (American Journal of Perinatology Reports, 2019)
Objectives The objective of this study was to determine the rate of dental caries and periodontal disease among gravid and recently postpartum women at five delivery centers within and surrounding Lilongwe, Malawi.Study Design We partnered with obstetric specialists, community health workers, and dentists to perform dental history interviews and dental examinations during the study period from December 2012 to May 2014. Dental examinations were performed according to World Health Organization standards to assess periodontal and oral health status.Results Among the 387 gravid and recently postpartum women, the rate of dental caries was 69.3% and the rate of composite dental disease (caries and periodontal disease) was 76.7%. The majority (69.5%) of women examined had a decayed-missing-filled (DMF) index greater than or equal to one; the average DMF Index was 2.48. The majority of women had never seen a dentist (62.8%). However, most did perform oral hygiene, two or more times per day (90.2%); most women reported brushing with toothpaste (88.1%).Conclusion When assessing this population for dental caries and periodontal disease, the rate of dental disease was high. Therefore, this may be an ideal setting to test for impactful interventions aimed at reducing caries and periodontal disease.
Keywords: pregnancy; preterm birth; Malawi; dental caries; periodontal disease; global health